Administration of Pancrelipase as Effective Treatment for Hepatic Steatosis After Pancreatectomy. Issue 6 (August 2015) - Kishi, Yoji; Shimada, Kazuaki; Nara, Satoshi; Esaki, Minoru; Kosuge, Tomoo
Abstract : Objectives: To evaluate the incidence of hepatic steatosis after pancreatectomy and whether pancrelipase improves steatosis more effectively than other conventional digestive enzymes. Methods: Patients who underwent distal pancreatectomy, pancreaticoduodenectomy (PD), or total pancreatectomy (TP) from August 2008 to July 2013 were included. Incidence of newly developed hepatic steatosis recognized by computed tomography and outcomes by treatment with pancrealipase or other enzymes were evaluated. Results: A total of 473 patients were evaluated. Among 366 patients who did not take any digestive enzymes until the recognition of steatosis or the last follow-up date, hepatic steatosis was recognized in 3% (4/130), 17% (38/229), and 45% (3/7) of patients after distal pancreatectomy, PD, and TP, respectively, during the median follow-up of 641 days. Seventy patients including 25 patients taking digestive enzymes showed hepatic steatosis and were treated with pancrelipase (20 patients), other enzymes (19 patients), or no enzyme (31 patients). Cumulative improvement rate after 1 year of treatment in the 3 groups was 92%, 51%, and 56%, respectively, and that of the pancrelipase group was significantly better than the other 2 groups. Conclusion: The risk of hepatic steatosis should be a concern after PD and TP. Treatment with pancrelipase was more effective compared to other enzymes.